High Prevalence of Sarcopenia in Women with Osteoporotic Fractures - Fernández, Candela (2016)
The aim of the present study was to assess the prevalence of sarcopenia in women with osteopenia/osteoporosiswith or without fragility fractures.Patients and methods: 112 ambulatory women with osteopenia/osteporosis were included. Body composition wasdetermined by DXA. Weight, height, body mass index (BMI), bone mineral density (BMD) of the total skeleton, totallean mass (LM), appendicular lean mass (ALM) and the index: appendicular lean mass/height² (ALM/h²) weredetermined. Grip strength and self-selected gait speed were assessed. Results: Average (X ± SD) results were: age70.9 ± 8.2 years, BMI: 23.1 ± 3.3 kg/h², total skeleton BMD T-Score:-1.7 ± 0.8, total LM 33.3 ± 3.8 kg, ALM 14.4 ±2.1kg and ALM/h²: 5.86 ± 0.68 kg/h². Walking speed 0.96±0.21m/s and handgrip: 18.8 ± 4.8 kg. The prevalence ofsarcopenia was: 24.7% (International Working Group criteria). Values for BMI, LM, ALM, ALM/h², gait speed andhand grip were significantly lower in sarcopenic vs. non-sarcopenic patients. 29 patients, average age: 70.5 ± 8.0years had osteoporotic fragility fractures (Fx). The prevalence of sarcopenia in the group of patients with Fx was41.4% vs. 19.3% in the non-Fx patients (n=83) (p<0.018).Conclusion: The prevalence of sarcopenia in women with osteopenia/osteoporosis was higher compared to thatusually reported in non-selected patients of similar age. Those with bone fractures had a significantly higherprevalence of sarcopenia compared to the non-fracture patients. The assessment of muscle mass and function inpatients with osteopenia/osteoporosis is recommended.